Hubungan Pelaksanaan Personal Hygiene dengan Tingkat Kepuasan Pasien Imobilisasi di Ruangan Neurologi RSUD Dr. Achmad Mochtar Bukittinggi Tahun 2015 - Kasrin, Rinawati; Berlian Putri, Rima (Jurnal Kesehatan - STIKes Prima Nusantara, 2015)
Satisfaction is feeling happy or upset someone who emerged after comparing the perception or impression of the performance or the result of a product and hopes. The ability of maintaining personal hygiene of patients by nurses were considered to improve patient satisfaction. Hygiene someone is an act to maintain the cleanliness and health both physical and psychological. Clients that have limited the success is always in need of personal hygiene for personal hygiene for the sake of her health needs and protected from germs in the room every hospital all patients in need of personal hygiene is very necessary for personal hygiene. Personal hygiene is in need once in daily activities especially on clients who are hospitalized with experienced immobilization. Initial survey conducted in 10 respondents were 7 respondents showed less personal hygienenya. This study aims to determine the relationship with the implementation of personal hygiene patient satisfaction level of immobilization. This research uses descriptive analytic design with cross sectional approach. In this study, the sample is as much as 52 respondents using a questionnaire measuring devices. The analysis is the analysis of univariate and bivariate with chi-square test. From these results obtained p value = 0,000